2023
DOI: 10.3390/ph16060865
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pyrrolo-Fused Heterocycles as Promising Anticancer Agents: An Integrated Synthetic, Biological, and Computational Approach

Abstract: Five new series of pyrrolo-fused heterocycles were designed through a scaffold hybridization strategy as analogs of the well-known microtubule inhibitor phenstatin. Compounds were synthesized using the 1,3-dipolar cycloaddition of cycloimmonium N-ylides to ethyl propiolate as a key step. Selected compounds were then evaluated for anticancer activity and ability to inhibit tubulin polymerization in vitro. Notably, pyrrolo[1,2-a]quinoline 10a was active on most tested cell lines, performing better than control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…These hydrogen bond interactions may provide the fundamental conditions for the reaction of caspase-9 with NCTD and 5-FU. Furthermore, we performed molecular dynamics simulations of both complexes for up to 10 ns [37], which revealed that both small molecules can form hydrogen bonds with caspase-9 (Figure S1D). Hydrogen bonding is a very strong non-covalent interaction that can reflect, to some extent, the binding strength between the ligand and the receptor.…”
Section: Network Pharmacological Analysis Showed That the Combination...mentioning
confidence: 99%
“…These hydrogen bond interactions may provide the fundamental conditions for the reaction of caspase-9 with NCTD and 5-FU. Furthermore, we performed molecular dynamics simulations of both complexes for up to 10 ns [37], which revealed that both small molecules can form hydrogen bonds with caspase-9 (Figure S1D). Hydrogen bonding is a very strong non-covalent interaction that can reflect, to some extent, the binding strength between the ligand and the receptor.…”
Section: Network Pharmacological Analysis Showed That the Combination...mentioning
confidence: 99%
“…As a result, the trend of the RGyr plot versus simulation time and its low fluctuation surely explain the residual backbone and how folding of the EGFR protein remained stable after interaction with compounds 2f and 2g. [35][36][37][38][39][40][41] An in silico study (Table 4) of the most biologically active synthesized compounds 2f and 2g has been assessed by Swiss ADME server. Lipinski's rule states that both investigated molecules satisfied this rule and thereby should be taken orally.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%
“…Our findings revealed that 2f and 2g could be good templates for further drug discovery and development. [35][36][37][38][39][40][41] An in silico study (Table 4) of the most biologically active synthesized compounds 2f and 2g has been assessed by Swiss ADME server. Lipinski's rule states that both investigated molecules satisfied this rule and thereby should be taken orally.…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%
“…Given the information discussed above, the focus of our current study is to synthesize new derivatives, building upon our previous research on N-heterocycle systems, [12][13][14] while remaining aligned with our keen interest in exploring chemical compounds with physiological activity. [15][16][17][18][19] This article presents our findings, including the synthesis, characterization, and antitumor evalution of several new N-heterocycle monoquaternary salts. Additionaly, we discuss two unexpected physical mixtures that formed during the process (Fig.…”
Section: Introductionmentioning
confidence: 99%